Eloise. Little Miss Christmas [videorecording (DVD)] - Archer, Wesley, 1961-; Mouser, Mary Matilyn, 1996-; Curry, Tim; Redgrave, Lynn, 1943-2010; Strong, Tara, 1973-; Bennett, Jeff, 1962-; Paulsen, Rob, 1956-; Tom, Lauren; Lillard, Matthew, 1970-; Thompson, Kay, 1909-1998 (Eloise., 2006)
Eloise and her hotel friends are putting on a Christmas show like no other. Using traditions from the different religions and cultures of her friends, they learn the true meaning of the season.